IMPLEMENTATION OF SERIOUS GAMES INSPIRED BY BALURAN NATIONAL PARK TO IMPROVE STUDENTS’ CRITICAL THINKING ABILITY - Putra, P. D. A.; Iqbal, M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
The purpose of this study is to implement Baluran National Park-based Serious Game to enhance the students' creative thinking skill and motivation to learn. The subject of the study were 60 students of SMP Negeri 1 Asembagus, Situbondo regency. The sample was divided into three groups. Two groups were chosen as experimental classes and the other group as the control class. Both of the experimental groups were given treatment using serious game based on Baluran National Park. The instruments used were observation sheet, pre-test, and post-test. Baluran National Parks-based serious game was effective in improving the students' creative thinking skill and motivation to learn science subjects.